2014
DOI: 10.1111/jpn.12252
|View full text |Cite
|
Sign up to set email alerts
|

Low ambient temperature elevates plasma triiodothyronine concentrations while reducing digesta mean retention time and methane yield in sheep

Abstract: Ruminant methane yield (MY) is positively correlated with mean retention time (MRT) of digesta. The hormone triiodothyronine (T3 ), which is negatively correlated with ambient temperature, is known to influence MRT. It was hypothesised that exposing sheep to low ambient temperatures would increase plasma T3 concentration and decrease MRT of digesta within the rumen of sheep, resulting in a reduction of MY. To test this hypothesis, six Merino sheep were exposed to two different ambient temperatures (cold treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Barnett et al (2012; 2015) reported a positive correlation of ambient temperature and a negative correlation of triiodothyronine (T 3 ) with MRT of digesta. In present study, although the T 3 level did not alter but the decline in thyroxin levels at 35°C and 40°C exposure suggested that the MRT of digesta was comparatively higher at theses temperatures.…”
Section: Results and Disussonmentioning
confidence: 97%
See 2 more Smart Citations
“…Barnett et al (2012; 2015) reported a positive correlation of ambient temperature and a negative correlation of triiodothyronine (T 3 ) with MRT of digesta. In present study, although the T 3 level did not alter but the decline in thyroxin levels at 35°C and 40°C exposure suggested that the MRT of digesta was comparatively higher at theses temperatures.…”
Section: Results and Disussonmentioning
confidence: 97%
“…In present study CH 4 emission decreased progressively with increase in temperature up to 35°C and then increased to initial levels. Barnett et al (2015) reported a positive correlation of ambient temperature and a negative correlation of triiodothyronine (T3) with CH 4 yield. In present experiment T3 level did not alter with increase in temperature hence, no correlation was established between T3 level and CH 4 emission in crossbred cattle.…”
Section: Results and Disussonmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on CH 4 in mammals stem from domestic ruminants, where CH 4 is, by contrast, mainly considered an unavoidable, unwelcome loss of energy and contribution to greenhouse gas emissions. As in humans, intra-specific variation in CH 4 production in ruminants has been linked to digesta retention: animals with longer digesta retention, either due to more voluminous rumens at similar intake, or due to lower intake at uncontrolled rumen capacity, generally produce more CH 4 per ingested DM (Pinares-Patiño et al, 2003;Goopy et al, 2014;Hammond et al, 2014;Barnett et al, 2015;Cabezas-Garcia et al, 2017). Here, however, it is the retention time that is considered the cause, where more time available is considered responsible for more fermentative digestion with an ensuing increased CH 4 production.…”
Section: Why Harbour Methanogens?mentioning
confidence: 99%
“…In essence, a higher food intake leads to a faster passage of digesta through the digestive tract, mostly because of the limited capacity of the gut to expand. A shorter MRT, in turn, was correlated with a lower CH 4 yield in various studies with sheep (Barnett et al, , 2015Goopy et al, 2013;Hammond et al, 2014;Pinares-Patino et al, 2003). Janssen (2010) summarized these findings, creating a model for the prediction of CH 4 yield that used a range of factors, including MRT.…”
Section: Effect Of Feeding Regimen and Kangaroo Species On Methane Emmentioning
confidence: 99%